2006
DOI: 10.1016/j.toxlet.2006.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke condensate induces cytochromes P450 and aldo-keto reductases in oral cancer cells

Abstract: Our objective is to identify molecular factors which contribute to the increased risk of smokers for oral squamous cell carcinoma (OSCC). In the present study, we investigated the effects of cigarette smoke condensate (CSC) on gene expression profiles in different human oral cell phenotypes: normal epidermal keratinocytes (NHEK), oral dysplasia cell lines (Leuk1 and Leuk2), and a primary oral carcinoma cell line (101A). We determined differential gene expression patterns in CSC-exposed versus non-exposed cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
107
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(117 citation statements)
references
References 35 publications
9
107
0
1
Order By: Relevance
“…6) and inhibiting some transporters like OATP1B1, OATP1B3, OCT1 and MATE1 (Fig. 1B) are similar to those used in previous studies with cultured cells, including human hepatic cells (Fields et al 2005;Nagaraj et al 2006;Xiao et al 2015); they also up-regulated the drug metabolizing enzymes CYP1A1 and CYP1B1, that, together with other AhR targets such as CYP1A2, constitute key targets induced by smoking in humans (Chang et al 2003;Dobrinas et al 2011;Thum et al 2006) and are in the range of CSC concentrations (20 to 120 ”g/mL) previously hypothesized to be relevant for human smokers (Gao et al 2005). On the other hand, 10-40 ”g/mL CSC corresponds to 0.768-3.072 ”g/mL (4.73-18.92 ”M) nicotine, when considering that CSC contains 7.68 % (weight/weight) nicotine (Eldridge et al 2015), and such nicotine concentrations are much higher than those (25 to 444 nM) commonly described in smoker blood (Russell et al 1980).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…6) and inhibiting some transporters like OATP1B1, OATP1B3, OCT1 and MATE1 (Fig. 1B) are similar to those used in previous studies with cultured cells, including human hepatic cells (Fields et al 2005;Nagaraj et al 2006;Xiao et al 2015); they also up-regulated the drug metabolizing enzymes CYP1A1 and CYP1B1, that, together with other AhR targets such as CYP1A2, constitute key targets induced by smoking in humans (Chang et al 2003;Dobrinas et al 2011;Thum et al 2006) and are in the range of CSC concentrations (20 to 120 ”g/mL) previously hypothesized to be relevant for human smokers (Gao et al 2005). On the other hand, 10-40 ”g/mL CSC corresponds to 0.768-3.072 ”g/mL (4.73-18.92 ”M) nicotine, when considering that CSC contains 7.68 % (weight/weight) nicotine (Eldridge et al 2015), and such nicotine concentrations are much higher than those (25 to 444 nM) commonly described in smoker blood (Russell et al 1980).…”
Section: Discussionsupporting
confidence: 76%
“…CSC, supplied by Murty Pharmaceuticals (Lexington, KY), was prepared by smoking University of Kentucky's 3R4F standard research cigarettes on a Federal Trade Commission smoke machine (Nagaraj et al 2006). Smoke particulates were collected on a glass fiber filter.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…Zhang and colleagues provide further in vivo evidence that many of these genes are down-regulated in persons who reported quitting smoking at least 1 year before the assessment (CYP1B1, AKR1C1, AKR1C2, AKR1B10, and ALDH3A1). Many of these same genes were previously shown to be overexpressed in oral cancer cells exposed to tobacco smoke condensate (8), in bronchial epithelial cells of smokers, and in patients' non-small cell lung carcinoma cells (9,10). The effects are also consistent with the effects of smoking on the airway transcriptome (11,12).…”
supporting
confidence: 61%
“…This is the first study to reveal an interaction between MMP1 1607 genotype and cigarette smoking on the susceptibility to oral cancer. Long-term tobacco smoking and areca chewing have been shown to contribute to etiology of oral cancer development (9,10,(41)(42)(43)(44). The results showed that gene-environment interaction was not obvious between MMP-8 genotypes and personal risk behaviors, alcohol drinking, cigarette smoking or areca chewing.…”
Section: Discussionmentioning
confidence: 99%